CLINICAL MANIFESTATIONS OF CYTOMEGALOVIRUS INFECTION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The work is based on the features of clinical manifestations of acute primary and reactivated forms of CMVI in children aged 1 to 3 years, observed on an outpatient basis. The main group and the comparison group included patients who applied for an appointment with an infectious disease doctor with symptoms of acute respiratory infection in the period 2021 to 2024 at the Bukhara Regional Infectious Diseases Hospital. With primary CMV infection, the acute period of the disease in young children proceeds according to the type of mononucleosis, the clinical picture of the reactivated form is nonspecific, accompanied by a prolonged fever with lymphadenopathy. Indirect laboratory markers of active CMVI are: neutropenia (46.1%), hypoimmunoglobulinemia A (49.0%) and G (51.0%).